ACTIVE SEARCH AT SCHOOL: STRATEGIES AND CHALLENGES IN STATE SCHOOLS OF ESPÍRITO SANTO (REMUNOM, 2024)
AbstractActive school search is a crucial strategy to combat exclusion and dropout, ensuring that students remain in school and receive quality education. In Espírito Santo, this practice faces historical and structural challenges but shows promising results when there is community involvement and intersectoral support, especiallyin adverse socioeconomic contexts. In view of the above, the study aims to analyze active school search practices in state schools in Espírito Santo and their impact on reducing school dropout. The methodology of this study is bibliographic in nature. To this end, the initial process involved the selection of academic and documentary sources that addressed the topic. The research was based on a survey of diverse materials, including scientific articles, institutional reports, publications in specialized journals and manuals for guiding educational practices. Thus, it is understood that the study reinforces that active school search is more than a monitoring tool; it is a comprehensive approach that promotes inclusion and ensures the right to education in an equitable and effective manner. Strengthening these practices, combined with consistent public policies and community engagement, is essential to consolidate a fairer educational system that is prepared to face future challenges.